Systemic lupus erythematosus, pulmonary hypertension, and left recurrent laryngeal nerve palsy. - Aszkenasy, O M (1987)
Pulmonary hypertension in systemic lupus erythematosus (SLE) is rare in the absence of parenchymal lung disease. We report such a case, which was complicated by the subsequent development of a left recurrent laryngeal nerve palsy, and in which there was a strong family history of SLE.